The Unloved Variable of Extraversion and Academic Achievement in SLA - Muhabat, Fakharh; Shahbaz, Muhammad (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study is based on extraversion vs. introversion and their relation with academic achievements. It is conducted to find effects of these two personality types in SLA. It is a qualitative type of research and descriptive method is used for this research. Eysenck's theory of personality is used as a theoretical framework. Data is collected through interview from twenty students studying at a public sector university. After analyzing the data, this research supports the claim of applied linguists who believe that extraversion has the advantage in second language learning and extroverts obtained higher marks. This research is beneficial for those future researchers who want to conduct research on personality types and achievement in Pakistan and elsewhere in the world.